Review of displacement–based seismic design methods of reinforced concrete regular frames - Varughese, Jiji Anna; Menon, Devdas; Prasad, A. Meher (Journal of Structural Engineering, 2025)
Structural displacement is now recognized as a key parameter for of structural and non-structural damage to a building during an earthquake. This paper reviews and compares some of the recently developed displacement-based seismic design (DBD) approaches, which promise a more rational design philosophy, compared to the conventional forcebased design (FBD). This paper reviews six displacement-based procedures, and compares their relative performance, as applied to the seismic design of typical reinforced concrete (RC) moment-resisting frames of 4, 9 and 15 storeys located in zone V. Despite all methods using the same set of design parameters, a large variation in design strength and member sizes is observed. It is found that Performance-based Plastic Design (PBPD) and Direct Displacement-based Design (DDBD) methods give the most economical designs. The performances of these two methods were assessed by time history analyses using ten spectrum compatible earthquakes and it is found that both methods achieve the desired performance levels. However, there is scope to carry out further research and improve on these displacement methods, particularly for taller building frames.